2007
DOI: 10.1182/blood-2007-03-067710
|View full text |Cite
|
Sign up to set email alerts
|

Myeloma bone disease and proteasome inhibition therapies

Abstract: Bone disease is one of the most debilitating manifestations of multiple myeloma. A complex interdependence exists between myeloma bone disease and tumor growth, creating a vicious circle of extensive bone destruction and myeloma progression. Proteasome inhibitors have recently been shown to promote bone formation in vitro and in vivo. Preclinical studies have demonstrated that proteasome inhibitors, including bortezomib, which is the first-in-class such agent, stimulate osteoblast differentiation while inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
104
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(110 citation statements)
references
References 73 publications
0
104
0
6
Order By: Relevance
“…20 Recent studies demonstrated that bone markers, which reflect osteoclast and osteoblast activity, can be modulated by novel agents such as proteasome inhibitors or immunmodulatory drugs. [21][22][23][24] Because of the clinical relevance of myeloma bone disease, we hypothesized that the bone resorption marker ICTP may add to the prognostic value of ISS. Thus, we evaluated the adverse prognostic impact of ICTP in combination with established prognostic factors in a patient cohort of 100 consecutive newly diagnosed patients with symptomatic MM.…”
Section: Introductionmentioning
confidence: 99%
“…20 Recent studies demonstrated that bone markers, which reflect osteoclast and osteoblast activity, can be modulated by novel agents such as proteasome inhibitors or immunmodulatory drugs. [21][22][23][24] Because of the clinical relevance of myeloma bone disease, we hypothesized that the bone resorption marker ICTP may add to the prognostic value of ISS. Thus, we evaluated the adverse prognostic impact of ICTP in combination with established prognostic factors in a patient cohort of 100 consecutive newly diagnosed patients with symptomatic MM.…”
Section: Introductionmentioning
confidence: 99%
“…Pre-clinical and clinical data have shown that bortezomib has a positive effect on bone remodeling by inhibiting osteoclast formation and stimulating osteoblast differentiation. [58][59][60][61] As bortezomib influence osteoclasts as well as osteoblasts and targets different mechanisms as HDACi, combining bortezomib with JNJ-26481585 would be a promising therapeutic strategy to improve the reducing effects of bortezomib on the development of MM-related bone disease.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] In addition to its direct inhibitory effects on the proteasome, 9 bortezomib has been noted to increase the level of intracellular reactive oxygen species (ROS) as an important component of its ability to induce apoptosis, [13][14][15][16][17][18] autophagy [19][20][21] and differentiation. 22 A sustained increase in ROS generation appears, in turn, to enhance the inhibitory effects of bortezomib on proteasomal activity. 9 It has also been postulated that the bortezomib-induced increases in ROS levels in tumor cells may be the basis for its synergy with other chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%